(untitled) (International journal of medical sciences, 2026)
Abdominal injuries are associated with significant morbidity and mortality, and their diagnosis and treatment remain complex and controversial. This study evaluated the effectiveness of endovideosurgery and enhanced surgical techniques for the diagnosis and treatment of hemodynamically stable and unstable patients with abdominal injuries. This study included 190 cases of abdominal injuries treated between June 2020 and June 2025. The main group underwent endovideosurgery and improved surgical techniques, while the comparison group was treated with traditional methods. The outcomes of the advanced surgical approach and endovideosurgery were assessed and compared with traditional methods to evaluate their clinical significance. The use of endovideosurgery and enhanced surgical techniques reduced the rate of exploratory surgery for abdominal injuries from 25.4% to 3.6% (a sevenfold reduction). Postoperative complications also showed a significant decrease in abdominal injuries from 30.5% to 7.1%. Dividing patients based on hemodynamic stability is crucial in the surgical management of abdominal injuries, facilitating the effective use of endovideosurgical techniques in appropriate patient categories.